Exercise considerations during Coronavirus disease 2019 (COVID-19) outbreak: A narrative review - Shirvani, H.; Rostamkhani, F. (Journal of Military Medicine, 2020)
The widespread outbreak of coronavirus (COVID-19) worldwide has raised concerns about physical activity and exercise. A review of research on physical training and viral infections shows that regular, moderate-intensity aerobic exercise (65-80% VO2max) increases antibody titers, lymphocyte proliferation, gamma interferon, immunoglobulin M, G, and natural killer cells production. It modulates the levels of inflammatory cytokines, chemokines and T cell-mediated immune response to the influenza virus. That is also associated with stronger and longstanding antibody responses to influenza vaccination in adults. Based on the available evidence and similarity of some of the signs and/or symptoms of Covid-19 to the H1N1 virus, it may be recommended for exercise during the outbreak. Firstly, it is reasonable to restrict heavy exercise at this stage, as the open window hypothesis may increase the susceptibility to infection. Secondly, healthy or asymptomatic individuals can exercise moderately with hygiene guidelines and benefit from improved immune function according to the J-shaped model. Third, people with mild upper respiratory tract symptoms (e.g., runny nose, sinus congestion, mild sore throat) can exercise lightly with precautions. Finally, one suspected of Covid-19 symptoms (e.g., fever, cough, severe sore throat, myalgia, shortness of breath, general fatigue) should avoid exercise.